Digital light processing of Si-based composite ceramics and bulk silica ceramics from a high solid loading polysiloxane/SiO2 slurry. Issue 14 (November 2021) - He, Chong; Liu, Xinger; Ma, Cong; Cao, Yueqi; Hou, Feng; Yan, Liwen; Guo, Anran; Liu, Jiachen
Highlights: A high solid loading polysiloxane (PSO)/SiO2 slurry had been developed and DLP printed into 3D-PSO/SiO2 precursor. More ceramic content can be preserved in the PSO/SiO2 precursor through a two-step argon-air sintering process. Si-based composite ceramics can be obtained through the two-step argon-air sintering process. Bulk 3D-silica ceramics can be DLP fabricated from the PSO/SiO2 slurry. The introduction of sintering aid NaF can promote the sintering between the PSO and SiO2 powders. Abstract: Nowadays, 3D polymer-derived silicon oxycarbide ceramics (SiOC) can be fabricated by the stereolithography method successfully. However, due to their intrinsically poor ceramic content and the large thermal shrinkage during the pyrolysis, it is difficult for the bulk 3D polysiloxane precursors to be pyrolyzed into dense 3D-ceramics. Herein, the ceramic content of the photocurable polysiloxane precursors was increased by adding a large amount of SiO2 powders into the low solid content epoxy-acrylic siloxane. After being added with proper dispersant, the viscosity of the high solid loading polysiloxane/SiO2 slurry can reach a proper level. Bulk 3D-silica ceramics with the wall-thickness around 8 mm can be conveniently fabricated from the polysiloxane/SiO2 slurry by stereolithography and a two-step sintering process. The addition of a proper sintering aid NaF can promote the 3D-PSO/SiO2 precursor to be converted into dense and crack-free 3D-silica ceramics with good mechanical proprieties.